Effects of Credit on Economic Growth, Unemployment and Poverty - Mangasa Augustinus Sipahutar (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2016)
Abstract             Effect of credit on economic growth, unemployment and poverty provides evidence from Indonesia on the role of banks credit for promoting economic growth and reducing both unemployment and poverty.  To document the link between banks credit and economic growth, we estimate a VAR model and variance decompositions of annual GDP per capita growth rates to examine what proxy measures of banks credit are most important in accounting for economic growth over time and how much they contribute to explaining economic growth.  We also estimate an ECM to document the relationship between banks credit to both unemployment and poverty. This paper revealed bi-direction causality between banks credit and economic growth.  Banks credit promotes economic growth and economic growth affects credit depth and financial development.  Furthermore, banks credit is a growth accelerating factor on Indonesian economic growth.  Banks credit is an endogenous growth and a good predictor on Indonesian economy.Our estimation model explained that credit allocated by banks increases business escalation to the real sectors then promotes economic growth, decreases unemployment rate through increasing in labor demanded, increases income and then decrease poverty.  This overall transmission mechanism just occurred through presence of banks credit by increasing money supply to the real sectors, promotes growth and social welfare. Keywords :  banks credit, economic growth, growth accelerating factor, poverty, unemployment JEL Classification : E51, E52, E58